Efficient Photoelectrochemical Water Splitting by g-C3N4/TiO2 Nanotube Array Heterostructures - Liu, Changhai; Wang, Fang; Zhang, Jin; Wang, Ke; Qiu, Yangyang; Liang, Qian; Chen, Zhidong (Nano-Micro Letters, 2018)
Well-ordered TiO2 nanotube arrays (TNTAs) decorated with graphitic carbon nitride (g-C3N4) were fabricated by anodic oxidization and calcination process. First, TNTAs were prepared via the anodic oxidation of Ti foil in glycerol solution containing fluorinion and 20% deionized water. Subsequently, g-C3N4 film was hydrothermally grown on TNTAs via the hydrogen-bonded cyanuric acid melamine supramolecular complex. The results showed that g-C3N4 was successfully decorated on the TNTAs and the g-C3N4/TNTAs served as an efficient and stable photoanode for photoelectrochemical water splitting. The facile deposition method enables the fabrication of efficient and low-cost photoanodes for renewable energy applications. Highlights: 1 Well-ordered TiO2 nanotube arrays (TNTAs) decorated with g-C3N4 were fabricated by anodic oxidization of titanium foil and calcination process. 2 The g-C3N4/TNTA heterojunction efficiently enhanced the photoelectrochemical activity for solar light-driven water splitting. Its photocurrent density and applied bias photon-to-current efficiency were, respectively, 0.86 mA cm−2 and 0.25%, about twofold higher compared with those of pristine TiO2 nanotube arrays. 3 The heterojunction expanded the optical absorption range of the TNTAs, accelerated the migration of carriers, and suppressed the recombination of photogenerated electron–hole pairs via an efficient band alignment between TiO2 and g-C3N4.